Keanekaragaman Jenis Burung Air di Hutan Mangrove Karang Sewu, Gilimanuk, Bali. - Pettalolo, Dhira Alfiah R.; Watiniasih, Ni Luh; Sari, Alfi Hermawati Waskita (Current Trends in Aquatic Science; Vol 3 No 2 (2020), 2020)
Water bird is a bird species that most of their lives depend on water for their habitat. The purpose of this research was to find out the types of waterbirds that are often encountered, the diversity of waterbird species and the types of water birds that are protected based on the IUCN Red List  that found in Karang Sewu Mangrove Forest, Bali. The birds are identified and counted twice a day, from 07.00-09.00 am and from 04.00-06.00 pm. There were 11 species of waterbirds were found belong to 7 families, with a total of 181 individuals. The species of water bird whcih often found was the Trinil Bedaran ( Xenus cinereus ), followed by the Trinil Ekor Kelabu ( Tringa brevipes ) and the Cekakak Sungai ( Todiramphus chloris ). The species diversity index (H’) on Burung Island and Kalong Island was classified as medium, while in Gadung Island it was classified as low. All species of water birds found in Karang Sewu Mangrove Forest are included in the IUCN Red List , there are eight species of birds in Least Concern (LC) category consisting of Cangak Laut ( Ardea sumatrana ), Cangak Australia ( Ardea novaehollandae ), Cekakak Sungai ( Todiramphus chloris ), Cerek Asia ( Charadrius veredus ), Dara Laut Jambul Besar ( Thalasseus bergii ), Kokokan Laut ( Butorides striata ), Kowak Malam Merah ( Nycticorax caledonicus ) and Trinil Bedaran ( Xenus cinereus ), one  species in Near Threatened (NT) category is Bangau Tong-Tong ( Leptoptilos javanicus ) and two species are in the Vulnerable (VU) category, namely Trinil Ekor Kelabu ( Tringa brevipes ) and Wili-Wili ( Esacus neglectus ).